2022
DOI: 10.3389/fmicb.2022.949597
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and integrated analysis of a comprehensive Pseudomonas aeruginosa PAO1 library of mutants lacking cyclic-di-GMP-related genes

Abstract: Pseudomonas aeruginosa is a Gram-negative bacterium that is able to survive and adapt in a multitude of niches as well as thrive within many different hosts. This versatility lies within its large genome of ca. 6 Mbp and a tight control in the expression of thousands of genes. Among the regulatory mechanisms widespread in bacteria, cyclic-di-GMP signaling is one which influences all levels of control. c-di-GMP is made by diguanylate cyclases and degraded by phosphodiesterases, while the intracellular level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 129 publications
0
13
0
Order By: Relevance
“…However, despite its thoroughly proven DGC activity 30,54 , lacking WspR per se did not influence the overall biomass but more on biofilm 3-D structure 23,24 . Therefore, the inactivation of WspR in strains without mutations in wspF may not be the optimal strategy solely from the perspective of its role in biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite its thoroughly proven DGC activity 30,54 , lacking WspR per se did not influence the overall biomass but more on biofilm 3-D structure 23,24 . Therefore, the inactivation of WspR in strains without mutations in wspF may not be the optimal strategy solely from the perspective of its role in biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…To generate a more in vivo- like environment, P. aeruginosa aggregates were grown in synthetic cystic fibrosis medium 2 (SCFM2), which is regarded as the most accurate pre-clinical model developed to mimic CF mucus so far 22 . In P. aeruginosa , 42 proteins were reported to contain GG(D/E)EF, EAL/HD-GYP, or dual domains 23,24 , of which WspR has been used as the target for all previously identified DGC inhibitors in P. aeruginosa . However, we found that deleting wspR in PAO1 did not affect the overall auto-aggregation level in SCFM2.…”
Section: Introductionmentioning
confidence: 99%
“…In combination they may provide similar, but independently regulated DGC/PDE activities, as does the dual functionality of DcpA in A. tumefaciens. In the two major model strains of P. aeruginosa , PA01 and PA14, mutants for their dcpA homologs (PA2780/PA1426970), both impact cdGMP-dependent phenotypes, although to different extents (42, 43). In all of these cases, the positioning of a pruR -type gene immediately upstream is consistent with a regulatory relationship with the downstream gene.…”
Section: Discussionmentioning
confidence: 99%
“…3a). In P. aeruginosa, BifA is a highly conserved PDE responsible for c-di-GMP hydrolysis, so its dysfunction would elevate c-di-GMP and increase bio lm formation [36][37][38] . Although this mutation was not predicted to modify BifA structure (Fig.…”
Section: A Loss-of-function Mutation In Bifa Drove the Adaptation To ...mentioning
confidence: 99%